5 Understanding the clinical implication of mismatch repair deficiency in endometrioid endometrial cancer through a prospective study. (13th November 2020) - Kim, S; Tone, A; Pollett, A; Kim, R; Cesari, M; Clarke, B; Eiriksson, L; Hart, T; Holter, S; Lytwyn, A; Maganti, M; Oldfield, L; et al.
Abstract : Objectives: Findings on impact of mismatch repair deficiency (MMRd) on patient outcomes in endometrial cancer (EC) have been inconsistent to date. The objective of this study was to compare oncologic outcomes between MMRd and MMR-intact (MMRi) endometrioid EC (EEC). Methods: Between 2015–2018, we prospectively recruited 668 EC cases from three cancer centers in Ontario, Canada. Tumors were reflexively assessed for MMR protein expression by immunohistochemistry (IHC). Clinicopathological, treatment and survival data were compared between MMRd and MMRi cases. Results: Out of 668, there were 496 EEC (74%), with 347 MMRi (70%) and 149 MMRd (30%) cases treated with surgery and with complete follow-up information. Median follow-up was 16.8 months (6–96 months). MMRd tumors tended to be grade 2 or 3 (56% vs. 29%, p<0.001), with propensity for lymphovascular space invasion (LVSI) (29% vs. 17%, p=0.004) and received more adjuvant treatment (45% vs. 33%, p=0.03). This group also had significantly lower 3-year RFS (78% vs. 89%, p=0.02) although there was no difference in OS (p=0.91). MLH1/PMS2 deficient tumors had the lowest 3-year RFS compared to intact and other MMRd tumors (76% vs. 89% vs 87%, p=0.02). After adjusting for age, stage, grade, use of adjuvant treatment, and LVSI status, MLH1/PMS2 deficiency was still associated with the lowest RFS (p=0.05). Conclusions: MLH1/PMS2 deficient EECs exhibit more aggressive features compared to other MMRd and MMRi cases, with worse RFS. This may indicate an inherent difference in tumor biology, suggesting the importance of individualized management based on tumor's molecular phenotype.